2018
DOI: 10.1182/blood-2018-99-118348
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Mutant Calreticulins As Rogue Cytokines Trigger Thrombopoietin Receptor Activation Specifically in CALR Mutated Cells: Perspectives for MPN Therapy

Abstract: Background Mutant calreticulins carrying the sequence translated after a +1 frameshift at the C-terminus are major drivers of myeloproliferative neoplasms (MPNs). These mutant CALRs bind and activate TpoR/MPL in cells co-expressing TpoR and mutant CALRs, resulting in persistent JAK2-STAT5 signaling. Whether mutant CALR proteins are secreted, thus acting in trans on other cells, is not known. Aims Our objectives were to: 1) assess the direct TpoR-mutant CALR interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…Data from independent laboratories have shown that mutant CALR protein requires MPL for signaling and factor-independent cell growth, and that the normal lectin domain of CALR is essential to bind glycosylated sites on MPL. [32][33][34] More recently, it was reported that both mutant and wild-type CALR proteins are present at higher levels in the plasma of myelofibrosis patients (compared to normal individuals), 35,36 and may function in a paracrine fashion by binding the extracellular domains of MPL to facilitate receptor dimerization. 34,36 However, the relative contribution of autocrine versus paracrine versus endosomal signaling of mutant CALR protein to aberrant activation of the JAK-STAT pathway in MPN has not been fully elucidated (Figure 1).…”
Section: Molecular Aspects Of Calr and Ruxolitinibmentioning
confidence: 99%
“…Data from independent laboratories have shown that mutant CALR protein requires MPL for signaling and factor-independent cell growth, and that the normal lectin domain of CALR is essential to bind glycosylated sites on MPL. [32][33][34] More recently, it was reported that both mutant and wild-type CALR proteins are present at higher levels in the plasma of myelofibrosis patients (compared to normal individuals), 35,36 and may function in a paracrine fashion by binding the extracellular domains of MPL to facilitate receptor dimerization. 34,36 However, the relative contribution of autocrine versus paracrine versus endosomal signaling of mutant CALR protein to aberrant activation of the JAK-STAT pathway in MPN has not been fully elucidated (Figure 1).…”
Section: Molecular Aspects Of Calr and Ruxolitinibmentioning
confidence: 99%
“…Interestingly, although CALR m has been shown to accumulate at the cell surface and be secreted, co-cultured and conditioned experiments did not detect MPL activation through secreted CALR m (39,41). However, a recent study using Nano-BRET and Nano-luciferase found that CALR m can act as a rogue cytokine and activate JAK-STAT signaling by binding in trans to surface MPL (50). Accordingly, CALR m is likely involved in MPL glycosylation and interacts with a specific form MPL during receptor maturation in the ER and in the Golgi apparatus, but not with the mature form.…”
Section: Calr Mutants' Role On Mpl Binding and Maturationmentioning
confidence: 99%
“…This new C-terminal sequence is rich in positively charged amino acids and, unlike unmutated CALR (which is located in the cytoplasm), these unique CALR -mutated peptides are transported to the cellular membrane and activate thrombopoietin receptor. They are even secreted and activate non-mutated cells, thus acting as the roque cytokines [43,44].…”
Section: Mutational Landscape Of Mpnmentioning
confidence: 99%